Nutritional Status and Diet Patterns of Children under-5 in select districts of Assam - Jith J R (CGIAR, 2022)
To understand the nutritional status of children under 5, complementary feeding practices, and diet patterns in districts of lower Assam, a region with a high incidence of malnutrition and maternal and child mortality. Part of a larger “Survey of Nutritional Status of Children under five in select districts of Assam”. A joint study by Directorate of Economics and Statistics Assam & Dept HSS IITG lead by Dr. Rajshree Bedamatta (Prof. Economics)